The role of ESG-based assets in generating the dynamic optimal portfolio in Indonesia - Kiki Nindya Asih; Noer Azam Achsani; Tanti Novianti; Adler Haymans Manurung (Cogent Business & Management, 2024)
The aim of this study is to evaluate the role of Indonesia's ESG-based equities (represented by ETF SRI-KEHATI) in achieving optimal portfolio diversification with different asset classes, i.e. conventional assets (equities and government bonds), safe-haven assets (gold), commodities (crude oil) and digital assets (Bitcoin). The data used in the study was the daily return of each asset from January 2018 to December 2023, representing data from before, during and the recovery after the COVID-19 pandemic. The methodology consists of a four-step process using the Pruned Exact Linear Time algorithm, the DCC-GARCH model and quadratic programming optimization. The study implies that investment managers and investors can reduce investment risk and balance their portfolios by including ESG-based assets in their portfolios. The study also urges investment managers to more actively manage their portfolios through rebalancing strategies. The results could also encourage policymakers to continue to support sustainable financing initiatives.
Keywords: C22; G11; Q59; 650; COVID-19; DCC-GARCH; dynamic portfolio; ESG-based equities; Indonesia